Tugas Kesehatan Keluarga dan Tingkat Kemandirian Keluarga di Wilayah Pesisir Kota Surabaya - Yoga Kertapati (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2019)
Family is the smallest unit of society that has a large influence on the health of each member of his family. The family is the focus of the approach in implementing the “Program Indonesia Sehat”. Families have assignments in the health sector to improve and maintain family health. One aspect that becomes a benchmark is the level of family independence. This study used a cross-sectional design with a sample of 150 families. Data analysis using the Spearman rho correlation test. The results showed that there was a positive correlation between family health duties and the level of family independence (r = 0.630, p = 0.000). Based on the results of this study, it is expected to be input and information about family health tasks as a measure of success in increasing family independence when providing family nursing care. Keywords: Family, Health Assignments, Level of Independence